2017
DOI: 10.1038/srep44926
|View full text |Cite
|
Sign up to set email alerts
|

Identification and comparative profiling of miRNAs in herbaceous peony (Paeonia lactiflora Pall.) with red/yellow bicoloured flowers

Abstract: Herbaceous peony (Paeonia lactiflora Pall.) is popular worldwide because of its gorgeous flower colour, and the yellow flower is the rarest. However, its mechanism of yellow formation is still unexplored from the post-translational level. In this study, the anatomy of the petal, cell sap pH and metal elements were investigated in bicoloured flower cultivar ‘Jinhui’ with red outer-petal and yellow inner-petal, and the yellow formation was influenced by the anatomy of petal, while not by the cell sap pH and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
(72 reference statements)
1
18
1
Order By: Relevance
“…Several miRNAs of different plant species, most with genome sequences, have been reported (Chu et al, 2016). In the present study, the number of miRNAs was similar to that in the P. ostii 'Feng dan' flower bud (Zhang et al, 2018); however, it was much greater than that reported for seed libraries of tree peony (Yin et al, 2018), and it was much less than that reported for miRNAs involved in flower coloration in P. lactiflora (Zhao et al, 2015(Zhao et al, , 2017. The reason why so few miRNAs were mapped might be the lack of tree peony genome sequences and the limited number of transcript data in public databases (Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Several miRNAs of different plant species, most with genome sequences, have been reported (Chu et al, 2016). In the present study, the number of miRNAs was similar to that in the P. ostii 'Feng dan' flower bud (Zhang et al, 2018); however, it was much greater than that reported for seed libraries of tree peony (Yin et al, 2018), and it was much less than that reported for miRNAs involved in flower coloration in P. lactiflora (Zhao et al, 2015(Zhao et al, , 2017. The reason why so few miRNAs were mapped might be the lack of tree peony genome sequences and the limited number of transcript data in public databases (Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 54%
“…For apple, in addition to three predictable MYBs, MdTAS4-siR81(-) also targets a bHLH TF that interacts with MdMYB10 to regulate anthocyanin biosynthesis (Xia et al, 2012). Furthermore, the miR156-SPLs module is conserved in anthocyanin biosynthesis in Litchi chinensis and P. lactiflora (Liu et al, 2017;Zhao et al, 2017). Although miRNAs have been investigated from the flower buds and seeds of tree peony cultivars, no systematic studies exploring miRNAs in the petals of P. ostii and P. rockii have been performed (Yin et al, 2018;Zhang et al, 2018).…”
mentioning
confidence: 99%
“…The blue coloration at the bottom of the inner perianth of T. gesneriana is attributed to Fe 2+ (Momonoi et al, 2009;Shoji et al, 2010). In red and yellow petals of Paeonia lactiflora, K, Ca, Mg, Mn, and Zn were abundant and showed significant correlation coefficient with the color indice h (Zhao et al, 2017). Although Ca, Mg, Fe, and Al were the most abundant metal ions in the Pd and Pl petals, only Fe and Al showed large differences between Pl and Pd, indicating that the different flower colors of P. delavayi might be related to Fe and Al.…”
Section: Discussionmentioning
confidence: 93%
“…The herbaceous peony (Paeonia lactiflora Pall.) is a flowering plant in the family Paeoniaceae, which is native to Central and eastern Asia (Zhao et al, 2018(Zhao et al, , 2017. Its dried diterpenes.…”
Section: Introductionmentioning
confidence: 99%